Human Action and Theory of Knowledge: A Necessary Reconciliation between Philosophy and Economics - Guimarães de Medeiros, José Edil (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
Resenha do livro: COSTA, João Martins Timóteo da. Ação humana e a teoria do conhecimento: uma leitura kantiana de von Mises. 2. ed. [S. l.]: Editora Escafandristas, 2022. 89 p.